2017
DOI: 10.1080/09603409.2017.1392112
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of pack cemented Ni2Al3 coating exposed to KCl(s) induced corrosion at 600 °C

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…This is discussed in more detail in Section 4.4. [35]. In the first year of plant testing, the nickel aluminide coating was protective on the majority of the circumference (Figure 13a), however after 2 years, there was no remaining protective nickel aluminide coating.…”
Section: Ni Coated Tubementioning
confidence: 98%
See 1 more Smart Citation
“…This is discussed in more detail in Section 4.4. [35]. In the first year of plant testing, the nickel aluminide coating was protective on the majority of the circumference (Figure 13a), however after 2 years, there was no remaining protective nickel aluminide coating.…”
Section: Ni Coated Tubementioning
confidence: 98%
“…Laboratory testing at 600 o C for 1 week in 5%O 2 +40%H 2 O+N 2 with KCl deposit of the nickel aluminide coating used in the power plant exposure revealed that there was reactivity between KCl and the Al 2 O 3 oxide formed on the coating[35]. The reaction rate observed in the laboratory exposures was very low, but the reaction would still lead to release of chlorine species that could with time propagate the corrosion attack observed in the plant exposed samples.…”
mentioning
confidence: 97%
“…Exposure of Ni2Al3 coatings on pure Ni with a small amount of KCl at 600 o C showed formation of a potassium, aluminium and oxygen rich corrosion product, but the extent of attack was minimal compared to AISI 304 austenitic stainless steel and pure Ni. 20 The investigations by Vokal et al…”
Section: Evaluated the Behavior Of Fe1-xal Fe2al5 Andmentioning
confidence: 99%
“…Thus coatings basing their protective behavior on aluminium have been developed utilizing pack cementation to aluminize both steels and nickel based alloys 50 . After the promising results of Nialuminides obtained on a laboratory scale 51,52 , the demonstration of the performance of these coatings under real service conditions in a biomass fired plant was undertaken for two years. After 1 year's exposure, the coatings had failed in a straw firing plant with 540 °C steam temperature 53 and the causes of failure were probably due to heavy thermal cycling resulting in spallation as well as local chemical breakdown of the protective scale.…”
Section: Future Materials Possibilitiesmentioning
confidence: 99%